Improvement of heat transfer in tube heat exchanger via passive flow generator / Farah Arina Ibrahim - Farah Arina , Ibrahim (2023)
Internally treated tube heat exchanger surfaces are one of the passive heat transfer enhancements that have attracted the attention of the industry due to their high performance and low-cost requirements. In this study, the effect of pipe internal groove surface and wire coil insertion on heat transfer, velocity profile, and thermal enhancement efficiency was numerically analyzed and simulated at two bulk temperatures of 25 °C and 30 °C. Three variations of 1000 mm copper tubes were analyzed numerically: smooth surface; groove diameters of 1 mm and 0.5 mm; and wire coil inserts of 1 mm and 0.5 mm. The pitch length was held constant at 8 mm. However, to support these, an experiment for 1 mm wire coil insertion was conducted and shows significant results on the enhancement of heat transfer. In simulation, the Nusselt number of a wire coil insert tube with a diameter of 0.5 mm increased by 114 % at a Reynolds number of 8000 and by 31 % at a Reynolds number of 4000. Compared to a smooth tube, a 1 mm circular groove increased the Nusselt number by 136 % and 19 % at Reynolds numbers of 20000 and 24000, respectively. Furthermore, 1 mm of circular groove tube increased the heat transfer coefficient from 12,000 to 24,000 by 45 % to 192 %. In the experiment analysis of a 1 mm wire coil insert tube, the friction factor decreased while the Nusselt number increased at bulk temperatures of 25 °C and 30 °C from 46 % to 197 %. The heat transfer coefficient increased between 2.94 and 2.97 times in comparison to the smooth tube. It is concluded that the diameter of the groove and wire coil play an important role in heat transfer improvement and convection on the boundary layer surface.